Da colônia Ijuhy à capital nacional das etnias: a multiplicidade étnica e a produção de memórias como fatores de desenvolvimento regional - Palma, Viviane da Rocha (My University, 2022)
This study asserts that in Ijuí, in the southern part of Brazil, there are three key elements that have demonstrated potential for regional development through tourism: ethnic multiplicity, the production of memories, and cultural heritage. This study addresses the relationships between these elements, their power in combination, and how they are employed in a deliberate way. The ethno-history of immigrants in the context of European migrations in the 19th century is evident within the territorial construction of this city. Social groups of different ethnicities experienced a new natural and cultural ecosystem as part of their territorial transposition westward. These groups were responsible for the insertion of different habits regarding language usage, commerce, agricultural production, craftmaking and architectural patterns that appear in construction. The multiculturality to which these immigrants were exposed "migrations and hybridizations" express a relationship with the formation of a regional identity and its use as a tourist attraction. The municipality of Ijuí was initially colonized by nineteen ethnic groups and displays marks of associativism, a characteristic resulting from this process. Therefore, the municipality brings together ethnic groups in the National Festival of Diversified Cultures - FENADI, currently in its 35th edition, which authorizes the area?s demarcation as a "Land of Diversified Cultures". This study applies an Oral History method and uses narrative interviews as a technique to analyze the actions of the ethnic groups that colonized Ijuí. Specifically, it identifies the processes by which they engaged with spatiality, emerging from the cultural borders established in the multiethnic interrelationships to which they were subjected since the beginning of colonization. As a result, the work asserts that there is a multiculturalism expressed through both materialities and immaterialities. For example, this multiculturalism is already recognized as cultural heritage by the State of Rio Grande do Sul and, since 2021, has had a federal seal; the municipality of Ijuí will soon be recognized as the National Capital of Ethnicities, as the city's integration of ethnic groups has proven to be a decisive factor for the development of local tourism. [resumo fornecido pelo autor]
O estudo aborda a relação entre a multiplicidade étnica, a produção de memórias e o patrimônio cultural que juntos e de forma planejada, tornaram-se elementos potenciais para o desenvolvimento regional, por meio do turismo, em Ijuí, no Sul do Brasil. A etno-história de imigrantes no contexto das migrações europeias do século XIX é prova da construção territorial desta cidade. Grupos sociais de diferentes etnias que na transposição territorial vivenciaram um novo ecossistema natural e cultural, foram responsáveis pela inserção de hábitos distintos em termos de língua, comércio, produção agrícola, ofícios e padrões arquitetônicos de construção. Essa multiculturalidade a que foram expostos "migrações e hibridizações" expressam relação com a formação da identidade regional e de sua utilização como atrativo turístico. O município de Ijuí foi colonizado inicialmente por 19 etnias e expressa marcas do associativismo como característica resultante deste processo. Portanto, o município reúne grupos étnicos na Festa Nacional das Culturas Diversificadas - FENADI, atualmente em sua 35ª edição, o que autoriza a denominação de "Terra das Culturas Diversificadas". O estudo utilizou como método a História Oral e fez uso de entrevistas narrativas como técnica a fim de analisar a ação dos grupos étnicos que colonizaram Ijuí e identificar os processos pelos quais construíram a espacialidade, a partir das fronteiras culturais estabelecidas na inter-relação multiétnica a qual foram submetidos desde os primórdios da colonização. Como resultado, observa-se a multiculturalidade expressa em materialidades e imaterialidades, já reconhecidas como patrimônio cultural do Estado do Rio Grande do Sul e, desde 2021, com chancela federal, o município de Ijuí passa a ser reconhecido como Capital Nacional das Etnias, tendo a integração dos grupos étnicos como fator decisivo para o desenvolvimento regional por intermédio do turismo local. [resumo fornecido pelo autor]
Keywords: Turismo - Ijuí (RS); Planejamento regional; Cultura e turismo; Patrimônio cultural; Ijuí (RS) - História; Tourism - Ijuí (Brazil); Regional planning; Culture and tourism; Cultural property; Ijuí (Brazil) - History